MECHANISM OF INNOVATIVE INFRASTRUCTURE OF SUPPORT OF SMALL BUSINESS DEVELOPMENT - L. Rudenko (Вестник университета)
The relevance of the stated theme is determined by the target setting of the Russian state to build a new economy of an innovative type, where small enterprises can become drivers of innovative development. The article investigates the issues of innovation development in Russia and in particular small innovative entrepreneurship. Based on the analysis of the current situation, the problems that hinder the innovative activity of small businesses have been identified, the main of which is the unformed mechanism of innovation infrastructure to support small business. The author’s interpretation of the mechanism of innovative infrastructure of support of small business has been offered. The сreated mechanism of innovation infrastructure to support small businesses can serve as the basis of scientific and instrumental approach to the formation of strategies and programs for the development of small innovative enterprises.